PERFORMANCE AND NUTRIENTS UTILIZATION PARAMETERS OF BROILER CHICKENS ADMINISTERED VARIED DOSAGES OF Ocimum gratissimum LEAF EXTRACT - Ndubuisi-Ogbonna, Lois Chidinma; Ibeh, Ifeanyi Boniface; Adeboye, Mark Minecha; Adesada, Ayodeji Qudus; Olumide, Martha Dupe; Akintunde, Adeyinka Oye (FUDMA JOURNAL OF SCIENCES, 2025)
Ocimum gratissimum leaf extract has potential as a natural growth promoter due to its rich phytochemical composition. The study evaluated the performance of broiler chickens administered varied dosages of O. gratissimum leaf extract (OGLE). The study was conducted at Teaching and Research Farm, Babcock University, Ilishan-Remo, Ogun State, Nigeria. Four treatments with four replicates were designed with varying dosages of OGLE (0, 0.2, 0.4 and 0.6 Ml/ liter of water). A total of 160 Arbor Acre broiler chicks were randomly assigned in a completely randomized design. The study assessed growth and nutrient utilization parameters. The results showed that the administration of OGLE significantly affected (p<0.05) final body weight, weight gain, total feed intake/bird and feed conversion ratio with birds in the 0.4 ml OGLE group having the best values for these parameters. Digestibility of lipid and crude fibre also followed a significantly positive trend (p<0.05) in T3. There was no significant variations (p>0.05) in relative weights of the liver, gizzard, heart, spleen, and intestinal length among the treatment groups. Birds administered 0.4 ml OGLE (T3) recorded significantly higher (p<0.05) proventricular temperatures (28.25 ± 0.05°C) than those in T4 (22.25 ± 1.45°C), jejunal and crop pH decreased significantly (p<0.05) with increasing OGLE levels. Birds in T4 (0.6 ml OGLE) recorded the lowest jejunal pH (3.20 ± 0.90). It is concluded that the oral administration of O. gratissimum leaf extract at 0.4 ml per bird/day positively influenced feed efficiency, and intestinal environment in broiler chickens without adverse effects on organ development.